Intercultural Communication Strategy of Minang Migrants in Panyabungan, North Sumatera: Building Harmony in Diversity - Nasution, Dina Syarifah; Zulfikar, Zulfikar; Hasibuan, Sri Wahyuni (Universitas Pahlawan Tuanku Tambusai, 2025)
This research employs a qualitative methodology with an ethnographic approach to analyze the intercultural communication strategies of Minangkabau migrants in Panyabungan, North Sumatra. Data were collected through in-depth interviews, participant observation, and document analysis to gain insights into migrants’ adaptation processes, identity formation, and integration into the local community. The study examines migration through three stages: emigration (push and pull factors), physical migration (adaptation challenges and cultural resilience), and immigration (integration and identity negotiation). Findings reveal that Minangkabau migrants utilize various strategies, including social engagement, cultural adaptation, and the use of social networks, allowing them to maintain their cultural identity while fostering harmonious relationships in their new environment. This research highlights the significance of intercultural communication in ensuring successful migration and social integration.